The Use of a 4.7 Mg Deslorelin Slow Release Implant in Male Dogs in the Field - Vasetska, Anastasiia; Koerber, Hanna; Pilgram, Caroline; Schuler, Gerhard; Aslan, Selim; Saral, Gulsah; Goericke-Pesch, Sandra (Georg Thieme Verlag KG, 2023)
Objective Slow-release GnRH agonist implants (SRI) are used for reversible medical downregulation of testicular function in male dogs as an alternative to surgery. The 4.7 mg deslorelin SRI should reduce testosterone after 6-8 weeks and induce castration-like effects for 6 months (mon). However, some individual variation is described in the field in regard to onset and duration of effect. For this reason, we aimed to study the effects of the 4.7 mg deslorelin SRI in a larger cohort.Material and methods In total 50 intact, healthy male dogs (12-48 months, mon; 9-40 kg) were treated with a 4.7 mg deslorelin SRI into the umbilical area (TG, n=45) or served as untreated controls (CG, n=5). CG dogs were surgically castrated after measurement of testicular dimensions and blood sampling for testosterone. In TG, SRIs remained for 5 mon in place and subsequently 3-7 male dogs were surgically castrated at removal (week, W 0) or 1, 2, 3, 4, 5, 6, 7, 8 or 10 weeks later. Examination parameters were testicular dimensions (before treatment, at 4, 8, 12 W, 5 mon, weekly until castration), testosterone (before treatment, at 8 W, 5 mon, castration) and testicular histology (castration).Results Whereas examination parameters did not differ between CG and TG before treatment, testicular volume and testosterone was significantly reduced at all time points during treatment. In all but 3 (8 W) and 2 male dogs (5 mon) testosterone was basal during treatment before removal, whereas the parameters were significantly reduced compared to pre-treatment in the respective dogs. After implant removal, testosterone and testicular volumes increased. However, different to earlier studies, the ,,restart" was more variable with individual basal testosterone until W7, but also physiological testosterone concentrations in W2. Similarly, histological testicular findings at castration were quite variable: besides an arrest on spermatogonia and spermatocytes, elongated spermatids with normal spermatogenesis were found in individual dogs.Conclusion Our study confirms the efficacy of the deslorelin SRI, but also individual variation especially regarding reversibility of effects on endocrine and germinative testicular function.
Vasetska, Anastasiia/0000-0001-5339-5577; Findik, Murat/0000-0003-1408-2548
Keywords: Hormonal Castration; GnRH Agonist Slow-Release Implant; Downregulation; Infertility